New strategy for improving heating uniformity and insect mortality in radio frequency treated mung beans - Li, Rui; Song, Xingyi; Guan, Xiangyu; Ni, Bo; Gao, Yu; Hou, Lixia; Kou, Xiaoxi; Wang, Shaojin (International Journal of Agricultural and Biological Engineering, 2022)
Radio frequency (RF) heating is usually used to control insects while maintaining the quality of harvested grains. Different packaging conditions may influence RF heating uniformity, insecticidal efficacy, product quality, and energy efficiency. An RF unit was used for conducting thermal treatments to evaluate the heating uniformity, the mortality of Rhizopathy dominica, the main quality attributes of mung beans under four packaging conditions, and the energy efficiency. The results show that after the aluminum foil sheet was added at the top or bottom side of bags, the RF heating uniformity was improved. The mortality of Rhizopathy dominica in mung beans was 100% for vacuum-packaged bags added with aluminum sheets on the bottom side and ordinarily sealed bags. The fastest cooling rate was observed in vacuum-packaged bags with aluminum foil sheets added at the top side. The energy efficiency of the RF system for treating mung beans in Packaging A, B, C, and D were 54.8%, 56.0%, 53.6%, and 54.8%, respectively. The effective RF treatment protocol was developed using vacuum-packaged bags with aluminum sheets added at the bottom side, 54°C hot air assisted RF treatment under an electrode gap of 13.5 cm for 5 min, holding for 6 min, and placing bags upward for cooling. The suitable packaging condition could be explored for developing practical RF disinfestation treatments.Keywords: heating uniformity, insect mortality, mung beans, packaging conditionsDOI: 10.25165/j.ijabe.20221505.7176Citation: Li R, Song X Y, Guan X Y, Ni B, Gao Y, Hou L X, et al. New strategy for improving heating uniformity and insect mortality in radio frequency treated mung beans. Int J Agric & Biol Eng, 2022; 15(5): 229–235.